2011
DOI: 10.1007/978-3-642-25453-6_43
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Use E-Government Services in Malaysia: Perspective of Individual Users

Abstract: Abstract. The growing need for convenience in the manner people conduct their activities in the 21st century, has popularized the notion of Internetenabled government services. Various governments now offer key services through the Internet, but what is still unclear, is the key to a successful egovernment platform. In this study, therefore, an extended Technology Acceptance Model (TAM) was used to underpin the development of a conceptual framework used to examine the influence of six independent variables (pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Certainly, many have acknowledged the merit and the influence of social influence (SI) as an important social force that shape strongly adoption decisions (Venkatesh et al, 2003;Shin, 2007;Eze et al, 2011;Yanping & Peng, 2012). Furthermore, the popular TAM3 has incorporated SI in their new expanded TAM model (Venkatesh & Bala, 2008).…”
Section: External Variables: Social Influence Trust Security/privacmentioning
confidence: 99%
“…Certainly, many have acknowledged the merit and the influence of social influence (SI) as an important social force that shape strongly adoption decisions (Venkatesh et al, 2003;Shin, 2007;Eze et al, 2011;Yanping & Peng, 2012). Furthermore, the popular TAM3 has incorporated SI in their new expanded TAM model (Venkatesh & Bala, 2008).…”
Section: External Variables: Social Influence Trust Security/privacmentioning
confidence: 99%
“…Venkatesh and Davis (2000) have concluded that subjective norm has a direct positive relationship with perceived usefulness. However, studies conducted in different social settings have reported that subjective norm has some empirical positive influence on behavioral intention (Eze et al, 2011;Sadi & Noordin, 2011). Specifically, many studies have found that subjective norm is a prime determinant in adoption of technology services provided by mobile devices (Linck et al, 2006;Shin, 2007;Gu et al, 2009).…”
Section: Technology Acceptance Model (Tam2)mentioning
confidence: 99%
“…Secondary data are pieces of information, which already exist. Examples of these will include articles in journals, magazines, newspapers, government publications, and industry analysis offered by websites, internet, and the media [29,30].…”
Section: E Brand Loyaltymentioning
confidence: 99%
“…Likert scale is used to measure how subjects strongly agree and strongly disagree with their statements on a 5-point scale. Likert point scale has been used in previous research as a measurement scale, for instance, study by Eze et al [29], Eze and Gilbert [30], Eze and Kam [31], Tsiotsou [33], and Chen [34].…”
Section: A Questionnaire Designmentioning
confidence: 99%